Sosialisasi Pemanfaatan Media Digital untuk Pemilahan Sampah Sebagai Inovasi dalam Meningkatkan Nilai Ekonomis Sampah Rumah Tangga di MTSN 1 Kota Padang - Belpani, Nur Suci Aryana; Hakiki, Syarah Nur; Oktaviani, Wulan; Hanoselina, Yulia (Orasi: Jurnal Ilmu Politik dan Sosial, 2025)
The unwanted leftover material after use is waste. The environmental issues in Indonesia today are undeniably related to the issue of waste that is not managed properly. The composition of waste in Indonesia is dominated by household waste. This waste cannot be avoided but can be reduced and managed properly. Efforts that can be made to minimize household waste are by sorting waste before disposal. Sorting includes sorting organic, non-organic and toxic waste. Currently, digital media can be used as an effective tool to encourage the sorting of household waste. So that sorting household waste according to its placement can minimize waste and can be used to increase economic value. Community Service activities carried out by students of the Department of Public Administration at MTSN 1 Padang City use counseling methods by delivering material, discussing and question and answer sessions. This activity aims to build awareness of MTSN 1 Kota Padang students of the importance of sorting household waste by utilizing digital media for sorting household waste to match the placement of the waste category.